Die Einheit von Wirtschafts- und Sozialpolitik in der Ära Honecker. Anspruch, Realität, Scheitern - Kai Müller (Journal on European History of Law, 2024)
The article discusses various aspects of the German Democratic Republic (GDR) under the leadership of Erich Honecker. The first text provides an overview of Honecker's political career, highlighting his role in consolidating power and maintaining the regime's stability. The second text examines the economic challenges the GDR faced, including the planned economy's inefficiencies, the lack of technological innovation, and the reliance on external borrowing. The third text focuses on the social policies implemented by the GDR government, particularly the housing program and other measures to improve the standard of living. The text shed light on the GDR's political, economic, and social dynamics under Honecker's rule.